Modelling client usage of e-statements: An empirical study in Malaysia - Bekhet H.A.; Al-Alak B.A.M. (Inderscience Publishers, 2023)
The objective of the current study was to investigate the major e-statement quality dimensions affecting the usage of e-statements by account holders in Malaysia, and to see how this use influenced behaviour. The study used a survey questionnaire distributed to a convenient sample of 1,000 bank account holders in Malaysia. An e-statement usage model was proposed based on a literature review and testing of two hypotheses. A multiple regression model was used to analyse the survey data. Only six predictor domains out of 13 were found to affect usage of the e-statements. It was also revealed that usage had a direct positive impact on behaviour. It was implied that financial institutions offering e-statement services should formulate bank marketing strategies that take into consideration e-statement quality dimensions that are highly evaluated by clients and which clients perceive as having the strongest impact on their usage of this service. © 2014 Inderscience Enterprises Ltd.